The development of technological usage of radio media - Herath, D.B. (University of Kelaniya, 2008)
The main objective of this study is to find out how the usage of technology has escalated in the radio media. In the early decade of 1920, right after the radio was introduced to the world, the radio media has made a significant technological development for. In the modem computer era the radio has to broaden up its radio traditions. The aim of this study is to find out why the radio media need this kind of technological backup for its upliftments . The study utilized secondary sources such as books and monthly magazines regarding the history of Sri Lankan radio. Also for the purpose of finding out how the technology has been used in the early ages of radio in Sri Lanka ,interviews with experts and participatory observation were used. In this study it is confirmed that the radio media has used technology as the most powerful means of confronting problem and challenges it faces. Not only in the radio engineering field , but also in the field of human resources , and also to clear up the defects in the field of creativity , technology has been used. In the recording process too it uses computer software and they have created unique software according to each radio station. With regard to the broadcasting process , radio stations are using computer software instead of using very expensive hardware. Hence , it has been used vastly in the competitive radio media to promote the institutional objectives,decrease creativity defects ,and finally to promote channels .
Keywords: Technology , Software , Radio , Computer , Editing